Creative concepts in psychology - Goldstein, Andrea H. (McGraw-Hill Education, 2011)
Creative Concepts in Psychology: An Activity and Case-based Approach looks at the study of psychology in a different way than more traditional Psychology text. Rather than place the bulk of the emphasis on concepts with only a few end-of-chapter activities, Creative Concepts in Psychology balances theory with application in a meaningful way. Every chapter provides the core pedagogy, but also devotes substantial time and energy to case studies and student activities. By merging these concepts so seamlessly, the ability to both learn and apply is mastered in every chapter.